Brain Gym Improves Cognitive Function for Elderly - Ah. Yusuf; Retno Indarwati; Arifudin Dwi Jayanto (Universitas Airlangga, 2010)
Introduction: The degradation of cognitive function present early dementia in elderly. Brain gym is one of the alternative implementation to improve the cognitive function of elderly. The objective of this study was to analyze the effect of brain gym to the improvement of cognitive function in elderly.Methods: This study used Quasy Experimental design. The populations were elderly in Social Service Unit Tresna Werdha Lamongan. The samples were recruited using purposive sampling, consist of 30 respondents, taken according to the inclusion criteria. Samples then divided into 2 groups, experimental groups and control groups. The independent variable of research this study was brain gym and the dependent variable was cognitive function at elderly. Data were collected by using MMSE score and then analyzed using Wilcoxon Signed Rank Test and Mann Whitney Test with level of significance α ≤ 0.05.Results: Result showed that there is an effect of brain gym to the improvement of cognitive function in elderly (p = 0.001). The difference of cognitive function also seen between experimental groups and control groups (p = 0.001).Conclusion: The conclusion of this research is brain gym improve cognitive function in elderly. The simple movement of brain gym able to coordinate the brain function so the brain activity become more optimal hence the improvement of memory function, recall and concentration.